1979
DOI: 10.1111/j.1365-2311.1979.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

The abundance and reproductive activity of common Carabidae in a winter wheat crop

Abstract: Abstract. 1. The number of common carabid beetles trapped‐irr a wheat field on a clay with flint soil from May to October in.1971–77 differed greatly: Harpalus rufipes and Pterostichus melanarius were numerous every year; but the appearance of H.aeneus, P.madidus, Agonum dorsale, Nebria brevicollis, Notiophilus biguttatus, Bembidion lampros and Trechus quadristriatus was much more variable.2. The numbers caught were not correlated with rainfall. Catches of the large species were positively correlated with acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
3
23
2
Order By: Relevance
“…Frank 197 1;Jones 1979). Similar yearly fluctuations have been observed frequently in studies with other crops (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Frank 197 1;Jones 1979). Similar yearly fluctuations have been observed frequently in studies with other crops (e.g.…”
Section: Resultssupporting
confidence: 81%
“…This might be particularly important for smaller species of ground beetles. Jones (1979) correlated the number of ground beetles collected in pitfall traps during a 6-yr study in winter wheat with accumulated air temperature Ͼ5ЊC. She found a negative correlation for small species, but a positive correlation for large species.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, smaller species common in agroecosystems (e.g., B. nitidum, B. obscurellum, B. quadrimaculatum) are diurnal, when daily values of relative humidity tend to be low. Hence, Jones (1979) concluded that temperature rather than humidity was more likely to affect the distribution of large species with the reverse being true for small species. Her conclusion is consistent with the greater capture of Bembidion spp.…”
Section: Discussionmentioning
confidence: 95%
“…The abundant species are common over geographic areas with similar climates but their abundance varies annually. This variation concerns not only local populations (den Boer, 1977;Jones, 1979) but also metapopulations of larger areas (Honek & Pulpan, 1983). Therefore the relative importance of local factors for determining species abun dance could only be revealed by a synchronous study.…”
Section: Introductionmentioning
confidence: 99%